Analysis on the Impact of Various Slope Ecological Restoration Techniques on Soil Fertility and Physicochemical Properties During the Summer Drought Period in Red Soil Area of Northeast Jiangxi Province - Lu Chao; Shao Zhichao; Liu An; Ma Jianrong; Sun Bowei (E3S Web of Conferences, 2024)
[Purpose] This study aims to investigate the impacts of three slope restoration techniques, namely, soil spray sowing, vegetation fiber, and vegetation concrete, on soil fertility, pH, and organic matter content during the summer drought period. The study also aims to explore the advantages of these three different restoration techniques, providing a basis for slope restoration in the Northeast Jiangxi region. [Methods] The study used experimental slopes established with three different restoration techniques: soil spray sowing, vegetation fiber, and vegetation concrete. Soil samples were collected during the rainy season in July 2022 and the drought season in September 2022. The changes in hydrolyzable nitrogen, available potassium, available phosphorus content, pH, and organic matter in the soil after restoration were comprehensively investigated. The study relies on the Qi-Wu expressway, and all the experiments are set on the slopes on both sides of the expressway. [Results]①For the soil restored using soil spray sowing during the drought season, the content of hydrolyzable nitrogen and available potassium was higher than that of the original soil, while the content of available phosphorus significantly decreased. The pH changed from acidic to weakly alkaline. ②For the soil restored using vegetation fiber during the drought season, although the content of available phosphorus increased, it was still relatively low. The content of available potassium decreased, but the total amount remained high. The content of hydrolyzable nitrogen was high and showed an increasing trend. The pH slightly decreased from weakly acidic to acidic. ③For the soil restored using vegetation concrete during the drought season, the content of hydrolyzable nitrogen, available potassium, and available phosphorus was high and showed an increasing trend. The pH slightly decreased, but it remained weakly alkaline before and after the drought. [Conclusion] Soil spray sowing, vegetation fiber, and vegetation concrete, all three restoration techniques, could demonstrate good performance during the drought period in the Northeastern Jiangxi region. In terms of their overall performance, the ranking from strong to weak is as follows: vegetation concrete > vegetation fiber > soil spray sowing. Soil spray sowing, as the most convenient and cost-effective slope restoration technique, could in the future incorporate additives that can improve local soil properties according to different regional characteristics. Vegetation fiber not only needs to improve soil acidity-alkalinity but should also appropriately incorporate phosphorus-containing additives. Vegetation concrete needs to address the issue of reducing soil acidity-alkalinity after restoration in the future.